Best practice mechanisms for biodiversity conservation law and policy - Callum Brockett; Katie Woolaston; Felicity Deane; Fran Humphries; Ethan Kumar; Amanda Kennedy; Justine Bell-James (Cambridge Prisms: Extinction)
Around the world, countries have introduced laws and policies designed to prevent species extinction. While there have been some success stories, overall, these laws and policies are routinely failing. Extinction rates continue to climb. However, the law is necessary to regulate the human-environment interactions that form the basis of the drivers of extinction and biodiversity loss, including land-clearing, the discharge of greenhouse gases and the introduction of invasive species. The purpose of this paper is to evaluate the literature specifically on biodiversity conservation law, to review and describe the commonalities in laws and legal systems that can be considered successful, or unsuccessful. Laws for the conservation of biodiversity form a critical component for minimising the drivers of extinction, with species extinction being an extreme outcome of biodiversity loss. We reviewed 128 publications from around the world to ascertain and synthesise best practices in law and policy that aim to protect and conserve biodiversity (herein termed ‘biodiversity conservation law’). The literature demonstrated that when it comes to biodiversity conservation law, the concept of ‘best practice’ is elusive, and does not necessarily equate to a reversal in species decline. Further, most western countries utilise the same legal mechanisms (also known as policy tools) for biodiversity conservation, although some countries implement these laws more effectively than others. In this paper, we explore and explain several common legal mechanisms discussed across the range of literature, including species listing and recovery plans, protected area regulation, stewardship, restoration, and offset and no net loss schemes. We also explore the necessity of biodiversity and climate mainstreaming across all laws and highlight the need to engage in genuine partnerships and collaborations with First Nations communities. This paper, and the principles explored herein, should assist law and policymakers to regulate more effectively and explain to those in the conservation sciences where research should be directed to improve the science-policy interface.